SEMIOTIC ANALYSIS OF BULLYING IN THE PYRAMID GAME SERIES ON SOCIAL MEDIA X - Nurlatifah, Putri Indah; Zahra, Tineziany; Nurfalah, Farida (International Journal of Social Service and Research, 2024)
Bullying is one of the social deviant behaviors that often occur in all environments, including schools. This study aims to determine the description of bullying and the meaning of signs contained in the series “Pyramid Game” on social media X through semiotics using Charles Sanders Pierce's theory. Each scene in this drama is decomposed into signs, objects, and interpretations that describe the dynamics of bullying behavior. The method used is descriptive qualitative, with a semiotic approach to analyze and explain how the meaning of signs regarding bullying occurs. The results of the analysis show various forms of bullying, ranging from physical violence, threats, sexual harassment, to social exclusion. Teachers have a major role in creating a safe, comfortable, and moral learning environment. Based on this research, it can be concluded that the importance of awareness and action to prevent and overcome bullying behavior, both in the school environment and society at large. Netizens responding to these scenes provide a deep understanding of the importance of awareness about negative behavior: bullying.